Water splitting via electrocatalysis and photocatalysis: Engineering stumbling blocks and advancements - Singh, Dalip; Kumawat, Srishti; Saini, Ajay; Sonia, Pankaj; Goyal, Ashish; Sravanthi, G.; Saxena, Kuldeep K.; Shaik, Saboor; Raja, Vijayanandh; Saleel, C. Ahamed; Agulut, Uemit (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
Renewable green hydrogen is produced using solar or wind-powered photocatalysis and electrocatalysis of water. In today's world, more than a third of nations have national plans for widespread green hydrogen generation. A variety of electrocatalytic water splitting methods exist such as alkaline water electrolyzer (AWE), proton exchange membrane (PEM), anion exchange membrane (AEM), solid oxide water electrolyzer (SOWE), and proton conducting ceramic electrolyzer (PCCEL). Nowadays, the high cost of producing hydrogen is a major barrier to the broad adoption of PEC and PEM, even though these processes are more efficient than conventional watersplitting technologies. A variety of carbon dopants, including graphene oxide, graphitic-carbon nitride, nanosheets, nitrogen, and other non-noble metals, are discussed in the present work and their applications in PEC and PEM catalysts. Based on the literature review, it is noticed that the hydrogen's levelized production cost (LCOH) for PEC is 8.43 USD/kg, whereas that for electrochemical water splitting systems is just 6.22 USD/kg. As a result, scientists are still looking for better, cheaper ways to produce green hydrogen. When combined with carbon dopants in catalysts, green hydrogen shows promise way as a sustainable energy source that can help bring the world closer to climate neutrality.
Keywords: Water splitting; Photocatalysis; Electrocatalysis; H 2 production; Green hydrogen; HYDROGEN EVOLUTION REACTION; GRAPHITIC CARBON NITRIDE; SOLAR HYDROGEN; RENEWABLE ENERGY; THIN-FILM; THERMOCHEMICAL PRODUCTION; ELECTROLYSIS CELLS; NANOSHEET ARRAYS; OXYGEN REDUCTION; RECENT PROGRESS; Chemistry; Electrochemistry; Energy & Fuels